2014
DOI: 10.1155/2014/656287
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Agrochemicals Intercalated into Montmorillonite Interlayer Space

Abstract: Periodic application of agrochemicals has led to high cost of production and serious environmental pollution. In this study, the ability of montmorillonite (MMT) clay to act as a controlled release carrier for model agrochemical molecules has been investigated. Urea was loaded into MMT by a simple immersion technique while loading of metalaxyl was achieved by a rotary evaporation method. The successful incorporation of the agrochemicals into the interlayer space of MMT was confirmed by several techniques, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Pereira et al described the preparation of a urea–montmorillonite nanocomposite by an extrusion process; urea release from the nanocomposites with urea contents of 50, 67 and 80% incubated in water for 5 days reached 68%, 90% and 78% of the initial contents, respectively. Similar formulations, but as micro‐ and nano‐particles, were investigated by Wanyika, showing that the fertiliser was completely released within a rather short time – no more than 10 days. Hamid et al used a urea/chitosan/bentonite system to prepare formulations containing 92% urea and various ratios of the fillers; the formulations were prepared by wet mixing of components followed by drying at 60 °C.…”
Section: Resultsmentioning
confidence: 79%
“…Pereira et al described the preparation of a urea–montmorillonite nanocomposite by an extrusion process; urea release from the nanocomposites with urea contents of 50, 67 and 80% incubated in water for 5 days reached 68%, 90% and 78% of the initial contents, respectively. Similar formulations, but as micro‐ and nano‐particles, were investigated by Wanyika, showing that the fertiliser was completely released within a rather short time – no more than 10 days. Hamid et al used a urea/chitosan/bentonite system to prepare formulations containing 92% urea and various ratios of the fillers; the formulations were prepared by wet mixing of components followed by drying at 60 °C.…”
Section: Resultsmentioning
confidence: 79%
“…Several other types of bacteria besides the one tested in the present study were studied. For instance, Cu−MMT composites were prepared and tested with E. coli and it was found they suppressed the growth of this organism [ 27 , 28 , 31 , 32 , 33 ]; this showed that the efficaciousness and ability of Cu-MMT were superior to Na-MMT [ 55 ]. Ag-MMT was also tested against mesophilic bacteria and bacteria present in lactic acid by Costa et al [ 34 ] and against E. faecium by Magaña et al [ 30 ], which showed it to be efficacious in all these cases.…”
Section: Resultsmentioning
confidence: 99%
“…Clay minerals possess good adsorption properties, cation exchange capacity (CEC) and also facilitate controlled delivery [ 27 ]. Antibacterial activity of metal exchanged montmorillonite composites such as Cu−MMT [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], Ag-MMT [ 29 , 34 ], and Zn−MMT [ 29 ] have been studied by various researchers. MMT-metal ion composites associated with polymers or resins have also been synthesized and tested [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al [77] reported the exfoliation of MMT clay into urea matrix, by extruded methods. Conversely, Wanika [78] could efficiently intercalate urea in the MMT by a simple immersion of the clay in urea solution.…”
Section: Montmorillonitementioning
confidence: 99%